O estudo do controle aversivo no Brasil: uma revisão de teses e dissertações entre 2014 e 2021 - Monori, Giovana Lima (2022)
The definition of the concept of aversive control has been a controversial issue in behavior analysis. An investigation of how Brazilian researchers have approached it could demonstrate how aversive control has been studied in this country. The objective of this study was to characterize Brazilian theses and dissertations presented from 2014 to 2021 that addressed the theme of aversive control. To achieve the results, the CAPES Theses and Dissertations Brazilian Database (in Portuguese, Banco de Teses e Dissertações da CAPES) was accessed and 62 Brazilian works on aversive control from the referred period were selected. The Brazilian institutions with the highest number of works on the subject were UFPA, USP, PUC-SP, UnB, PUC-GO, and UEL. The advisor with the highest number of works was Marcus Bentes de Carvalho Neto. More than two-thirds of the studies were the basic research type, and among them, the majority used human participants. The most used aversive stimulus was the loss of points or items, manipulated only for human participants. Out of the 15 studies that used non-human subjects, 14 used rats, and nine manipulated electrical shocks. It is expected that this study contributes to the characterization of the research about aversive control in Brazil as well as to identify trends and gaps that help in planning further works on the theme